A composite electrocatalyst and its preparation method and application
Through the composite electrocatalyst modified nickel phosphide ultra-thin nanosheets modified by iridium microcrystals, the high applied voltage and safety hazards in the hydrogen production process of water electrolysis are solved, and excellent electrochemical activity and ethanol oxidation reaction performance in alkaline solutions are achieved. , improving the stability and cost-effectiveness of the catalyst.
Patent Information
- Application Number
- CN202311116301.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-31
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2043-08-31
AI Technical Summary
The existing electrocatalysts require high applied voltages during the electrolytic hydrogen production process, which poses safety risks, and are difficult to have excellent catalytic activity in the oxidation reaction of hydrogen evolution and ethanol at the same time.
Ni(OH)2 ultrathin nanosheets were prepared by cyanoglycoal-NaBH4 method using iridium (Ir) microcrystal modified nickel phosphide (Ni2P) ultrathin nanosheets, and in situ reduction and phosphating treatment were performed to form Ir microcrystalline modified Ni2P ultra-thin nanosheets combine structural design to improve catalytic activity and electrical conductivity.
It exhibits excellent electrochemical activity in alkaline solutions, reduces the applied voltage required for hydrogen production by electrolyzing water, improves the catalytic performance of ethanol oxidation reaction, reduces safety risks, and improves the stability and cost-effectiveness of the catalyst.
Smart Images

Figure CN117230478B_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of electrocatalytic materials, and mainly to a composite electrocatalyst and a preparation method and application thereof. Background Art
[0002] Hydrogen energy is an important part of the future national energy strategy. Its industry is developing rapidly and has broad prospects. Electrolysis of water to produce hydrogen is one of the efficient ways to produce hydrogen, so it has attracted much attention. Hydrogen evolution reaction (HER) and oxygen evolution reaction (OER) constitute water decomposition reactions, and the reaction energy barriers are relatively high. If other chemical oxidation reactions are used instead of OER, it is expected to reduce the external voltage required for hydrogen production, reduce energy consumption, and achieve the co-production of high value-added chemicals. It also solves the safety hazards caused by the mixing of cathode and anode products in the hydrolysis cell, reduces safety risks, and is cheap and its electrochemical reforming is competitive in efficient hydrogen production. However, the use of ethanol oxidation reaction (EthOR) instead of OER requires electrocatalysts to have good HER and EthOR catalytic activity at the same time.
[0003] Therefore, the prior art still needs to be improved and developed. Summary of the invention
[0004] In view of the above-mentioned deficiencies in the prior art, the purpose of the present application is to provide a composite electrocatalyst, a preparation method and an application thereof. The composite electrocatalyst is an iridium (Ir) microcrystal-modified nickel phosphide (Ni2P) ultrathin nanosheet composite electrocatalyst (Ir-NCs / Ni2P-NSs), which exhibits excellent electrochemical activity for both HER and ethanol oxidation reaction (EthOR) in alkaline solution, aiming to provide an electrocatalyst having both good HER and EthOR catalytic activity.
[0005] The technical solution of this application is as follows:
[0006] A method for preparing a composite electrocatalyst, comprising the following steps:
[0007] S1, preparation of Ni(OH)2 ultrathin nanosheets;
[0008] S2, modifying the Ni(OH)2 ultra-thin nanosheets with iridium microcrystals by an in-situ reduction method to obtain Ni(OH)2 ultra-thin nanosheets modified with iridium microcrystals;
[0009] S3, phosphating the Ni(OH)2 ultrathin nanosheets modified with iridium microcrystals to obtain Ni2P ultrathin nanosheets modified with iridium microcrystals, i.e., the composite electrocatalyst.
[0010] The iridium microcrystal-modified Ni2P ultrathin nanosheets prepared by the preparation method of the composite electrocatalyst provided in the present application, the Ir microcrystals are uniformly dispersed on the Ni2P ultrathin nanosheets, the Ni2P ultrathin nanosheets modified with atomic-level thick Ir microcrystals can expose more active sites during the electrocatalytic reaction, nickel phosphide has excellent catalytic performance, and Ir has high conductivity. The combination of the two plus the structural design makes the composite electrocatalyst of the present application have sufficient active sites, conductivity, and catalytic activity.
[0011] The preparation method of the composite electrocatalyst, wherein the mass ratio of nickel element to iridium element in the Ni2P ultrathin nanosheet modified with iridium microcrystal is 20-100:1, the thickness of the Ni2P ultrathin nanosheet is between 1.5-2.5 nm, and the diameter of the iridium microcrystal is 3-5 nm.
[0012] The iridium microcrystal-modified Ni2P ultrathin nanosheets prepared in the present application have good EthOR performance of the electrocatalyst when the mass ratio of nickel element to iridium element in the iridium microcrystal-modified Ni2P ultrathin nanosheets is 20-100:1.
[0013] The method for preparing the composite electrocatalyst, wherein step S1 specifically comprises the following steps:
[0014] At room temperature, take nickel chloride solution and nickel potassium cyanide solution and mix them evenly, let them stand for 6-12 hours to obtain blue jelly-like NiCl2-K2Ni(CN)4 mixed cyanide glue;
[0015] Pour the NaBH4 solution into the NiCl2-K2Ni(CN)4 mixed cyanide gel, stir vigorously in a 60-80°C water bath for 3-7 hours, collect the precipitate by centrifugation to obtain the Ni(OH)2 ultra-thin nanosheets, wash them alternately with deionized water and 0.1 M KOH several times, and dry them at 50-60°C.
[0016] The preparation method of the composite electrocatalyst, wherein the molar ratio of nickel chloride to nickel potassium cyanide is 2:1, the concentration of the nickel chloride solution is 1-2 mM, the concentration of the nickel potassium cyanide solution is 0.5-1 mM, the concentration of the NaBH4 solution is 0.1-2 g / ml, and the ratio of the sum of the molar ratios of the NaBH4 to the nickel chloride and the nickel potassium cyanide is 10-30:1.
[0017] The method for preparing the composite electrocatalyst, wherein step S2 specifically comprises the following steps:
[0018] Dispersing the Ni(OH)2 ultrathin nanosheets and iridium source in deionized water, and ultrasonically treating until the mixture is uniform;
[0019] Add NaBH4 solution and stir in a water bath at 50-70℃ for 4-10 hours;
[0020] The Ni(OH)2 ultra-thin nanosheets modified with the iridium microcrystals are collected by centrifugal washing.
[0021] The preparation method of the composite electrocatalyst, wherein the mass ratio of the nickel element in the Ni(OH)2 ultra-thin nanosheet to the iridium element in the iridium source is 20-100:1; the concentration of the NaBH4 solution is 0.05-10 g / ml, the molar ratio of the NaBH4 to the iridium element is 550-3500:1, and 10-300 ml of the deionized water is added to every 100 mg of the Ni(OH)2 ultra-thin nanosheet.
[0022] The method for preparing the composite electrocatalyst, wherein step S3 specifically comprises the following steps:
[0023] In an argon atmosphere, the phosphite and the iridium microcrystal-modified Ni(OH)2 ultrathin nanosheets are placed in crucibles at the upper and lower tuyere of a tubular furnace, respectively, and then heated to 300-320°C at a rate of 1-5°C / min and kept warm for 1-2 hours to obtain the iridium microcrystal-modified Ni2P ultrathin nanosheets.
[0024] The method for preparing the composite electrocatalyst comprises the following steps: using 0.1-0.5 g of phosphate salt for every 0.1 g of the iridium microcrystal-modified Ni(OH)2 ultra-thin nanosheets; the phosphate salt is one of sodium phosphate, sodium hypophosphite, and potassium phosphate.
[0025] A composite electrocatalyst is prepared by the composite electrocatalyst preparation method as described above.
[0026] An application of the composite electrocatalyst as described above, wherein the composite electrocatalyst is used for electrolysis of water to produce hydrogen or ethanol oxidation reaction.
[0027] Beneficial effects: The preparation method of the composite electrocatalyst provided in the present application, the prepared composite electrocatalyst is an iridium microcrystal-modified nickel phosphide ultra-thin nanosheet composite electrocatalyst, which exhibits excellent electrochemical activity for both HER and ethanol oxidation reactions in alkaline solutions, and can be applied to water electrolysis to produce hydrogen or ethanol oxidation reactions. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 This is the TEM image of Ir-NCs / Ni2P-NSs synthesized in Example 1 of the present application.
[0029] Figure 2 It is the LSV curve of the HER performance test of each catalyst in Example 1 and Comparative Examples 1-5 of the present application.
[0030] Figure 3 It is the LSV curve of the EthOR performance test of each catalyst in Example 1 and Comparative Examples 2 and 4 of the present application.
[0031] Figure 4 LSV curves of Ir-NCs / Ni2P-NSs||Ir-NCs / Ni2P-NSs and Pt / C||RuO2 electrolyzers in different electrolytes.
[0032] Figure 5 NMR spectra of the electrolyte before and after chronoamperometry. DETAILED DESCRIPTION
[0033] The present application provides a composite electrocatalyst and a preparation method and application. To make the purpose, technical solution and effect of the present application clearer and more specific, the present application is further described in detail below. It should be understood that the specific embodiments described herein are only used to explain the present application and are not used to limit the present application.
[0034] The role of electrocatalysts in hydrogen production electrolyzers is crucial. They are the place where electrochemical reactions occur and the fundamental factor that determines the hydrogen production efficiency of hydrogen production electrolyzers. At present, the precious metal Pt exhibits significant HER performance, but its cost is high. Transition metal-based phosphides are considered to be a highly efficient and low-cost electrocatalyst for water electrolysis. Their catalytic activity can be further improved through structural design and surface modification of highly conductive materials. However, the electrocatalytic performance of existing transition metal-based phosphides still cannot meet the requirements of industrial applications, and their electrocatalytic performance needs to be improved.
[0035] The present application provides a method for preparing a composite electrocatalyst. An Ir microcrystal-modified Ni2P ultrathin nanosheet composite electrocatalyst Ir-NCs / Ni2P-NSs is prepared by a cyanoacrylate-NaBH4 method, in-situ reduction and subsequent phosphating process. The composite electrocatalyst exhibits excellent electrochemical activity for both HER and ethanol oxidation reactions in alkaline solutions.
[0036] Specifically, the method for preparing the composite electrocatalyst of the present application comprises the following steps:
[0037] S1. Preparation of Ni(OH)2 ultrathin nanosheets (Ni(OH)2-NSs).
[0038] In the present application, the cyanoacrylate-NaBH4 method is used to prepare Ni(OH)2 ultra-thin nanosheets, specifically, the following steps are included:
[0039] At room temperature, take nickel chloride solution and nickel potassium cyanide solution and mix them evenly, let them stand for 6-12 hours to obtain blue jelly-like NiCl2-K2Ni(CN)4 mixed cyanide glue;
[0040] Pour the NaBH4 solution into the above-mentioned mixed cyanoacrylate gel, stir vigorously in a 60-80°C water bath for 3-7 hours, collect the precipitate by centrifugation to obtain black Ni(OH)2 ultrathin nanosheets, wash them alternately with deionized water and 0.1 M KOH several times, and dry them at 50-60°C.
[0041] In this step, the molar ratio of nickel chloride to nickel potassium cyanide is 2:1, the concentration of the nickel chloride solution can be 1-2mM, and the concentration of the nickel potassium cyanide solution can be 0.5-1 mM. The solute of the nickel chloride solution can be NiCl2·6H2O or NiCl2. NaBH4 is used as a reducing agent, and NaBH4 can be stable at room temperature and pressure, has a mild reaction and has selective reducing properties. The concentration of the NaBH4 solution can be 0.1-2 g / ml, and the ratio of the sum of the molar ratios of NaBH4 to nickel chloride and nickel potassium cyanide can be 10~30:1.
[0042] In the present application, Ni(OH)2 ultra-thin nanosheets are prepared by the cyanoacrylate-NaBH4 method. Cyanide acrylate is a type of Prussian blue coordination polymer obtained by cyanide bridging, which can be synthesized by metal chloride and transition metal cyanide through coordination-substitution reaction. The subunits in cyanide acrylate serve as templates to promote the formation of ultra-thin nanosheets. The Ni(OH)2 ultra-thin nanosheets prepared by the above steps and raw materials have a thickness range of 1.5-2.5 nm.
[0043] S2. Ir microcrystal modification on Ni(OH)2 ultrathin nanosheets by in situ reduction method.
[0044] In the present application, step S2 specifically includes the following steps:
[0045] Ni(OH)2-NSs and iridium source were dispersed in deionized water and ultrasonicated until mixed uniformly;
[0046] Add NaBH4 solution and stir in a water bath at 50-70℃ for 4-10 hours;
[0047] Ni(OH)2 ultrathin nanosheets modified with Ir microcrystals (Ir-NCs / Ni(OH)2-NSs) were obtained by centrifugal washing.
[0048] In this step, the mass ratio of nickel in Ni(OH)2-NSs to iridium in iridium source is 20-100:1, the concentration of NaBH4 solution can be 0.05-10 g / ml, the molar ratio of NaBH4 to iridium can be 550-3500:1, and 10-300 ml of deionized water is added to every 100 mg of Ni(OH)2 ultra-thin nanosheets. This step is to modify Ir microcrystals on the Ni(OH)2 ultra-thin nanosheets prepared in step S1. With this raw material combination and dosage ratio, the iridium salt can be gently and fully reduced, so that the Ir microcrystals are uniformly dispersed on the surface of the Ni(OH)2 ultra-thin nanosheets, and the diameter of the generated Ir microcrystals is 3-5 nm. NaBH4 is used as a reducing agent to reduce Ir, which is consistent with the reducing agent used in the preparation process of step S1, which helps the system not to be affected by other factors.
[0049] The iridium source may be iridium chloride, which may be IrCl3·3H2O or IrCl3.
[0050] S3, phosphating treatment to obtain Ir microcrystal-modified Ni2P ultrathin nanosheets (Ir-NCs / Ni2P-NSs).
[0051] In the present application, step S3 specifically includes the following steps:
[0052] In an argon atmosphere, phosphite and Ir-NCs / Ni(OH)2-NSs were placed in crucibles at the upper and lower tuyere of a tube furnace, respectively. The temperature was then raised to 300-320°C at a rate of 1-5°C / min and kept at that temperature for 1-2 hours to obtain Ir microcrystal-modified Ni2P ultrathin nanosheets.
[0053] In this step, the prepared Ir microcrystal-modified Ni2P ultrathin nanosheets are the composite electrocatalyst of the present application, wherein the Ir / Ni mass ratio is 1-5%, preferably 3%.
[0054] In this step, 0.1-0.5 g of phosphite salt can be used for every 0.1 g of Ir-NCs / Ni(OH)2-NSs, which can ensure sufficient phosphating and phosphating process safety.
[0055] The phosphate salt may be one of sodium phosphate, sodium hypophosphite, and potassium phosphate, which can decompose at high temperature to produce phosphorus-containing vapor.
[0056] In this step, the temperature is raised to 300-320°C for reaction. Firstly, it can provide the temperature required for thermal decomposition of phosphate salts, and secondly, it can ensure that the phosphide phase of nickel is Ni2P. If the reaction temperature exceeds 330°C, other products will appear.
[0057] The Ir microcrystal-modified Ni2P ultra-thin nanosheets of the present application, wherein the mass ratio of nickel to iridium is 20-100:1, can be regulated by changing the amount of each material used in step S2. Compared with the Ir-free Ni2P ultra-thin nanosheet electrocatalyst, when the mass ratio of nickel to iridium in the Ir microcrystal-modified Ni2P ultra-thin nanosheets of the present application is 100:1, the EthOR performance of the electrocatalyst can be greatly improved, and the performance is best when the amount of Ir is 3%. As the amount of Ir gradually increases to a mass ratio of nickel to iridium of 20:1, the EthOR performance at high current density drops slightly, but is still much higher than that of the Ir-free Ni2P ultra-thin nanosheets.
[0058] The composite electrocatalyst of the present application has an Ir microcrystal diameter of 3-5nm, a Ni2P ultra-thin nanosheet thickness of 1.5-2.5nm, and the Ir microcrystals are uniformly dispersed on the Ni2P ultra-thin nanosheets. Compared with existing bulk catalyst materials, the Ni2P ultra-thin nanosheets modified with atomic-level Ir microcrystals of the present application will expose more active sites during the electrocatalytic reaction. Nickel phosphide has excellent catalytic performance, but poor intrinsic conductivity, while Ir has high conductivity. The combination of the two and the structural design make the composite electrocatalyst of the present application have sufficient active sites, conductivity, and catalytic activity.
[0059] The composite electrocatalyst prepared by the above method has the following advantages:
[0060] 1. 2D structure: large surface area and sufficient sites, which improves the catalytic activity and stability of the composite electrocatalyst;
[0061] 2. Nickel phosphide: HER catalytic performance is comparable to that of precious metal-based electrocatalysts, but the cost is relatively lower;
[0062] 3. Iridium: Improves overall conductivity;
[0063] 4. Electronic synergy between nickel phosphide and iridium;
[0064] 5. The composite electrocatalyst of the present application exhibits excellent electrochemical activity for both HER and ethanol oxidation reaction (EthOR) in alkaline solution, and the ethanol oxidation reaction can be used to replace the oxygen evolution reaction, so that the external voltage required for the electrolyzer is reduced, the added value of the anode product is increased, and the risk of hydrogen and oxygen mixed explosion is reduced. Among them, the composite electrocatalyst of the present application is not limited to ethanol oxidation reaction, and can also be used for oxidation reactions of methanol, glycerol, etc.
[0065] The present application also provides a composite catalyst, which is prepared by the above composite electrocatalyst preparation method. Further, the present application also provides the application of the composite electrocatalyst, which is used for water electrolysis to produce hydrogen or ethanol oxidation reaction.
[0066] The present application is further described below through specific examples.
[0067] Example 1
[0068] S1. Preparation of Ni(OH)2-NSs:
[0069] At room temperature, NiCl2 solution (1 mL, 1 M) and K2Ni(CN)4 solution (1 mL, 0.5 M) were mixed evenly and allowed to stand for 4 hours to obtain a blue jelly-like NiCl2-K2Ni(CN)4 mixed cyanide gel;
[0070] Pour NaBH4 solution (10 mL, 0.13 g / mL) into the above mixed cyanoacrylate gel and stir vigorously in a 70°C water bath for 5 h. Collect the precipitate by centrifugation to obtain black Ni(OH)2 ultrathin nanosheets, wash them alternately with deionized water and 0.1 M KOH several times, and dry them at 60°C.
[0071] S2. Ir microcrystal modification on Ni(OH)2-NSs:
[0072] 100 mg of Ni(OH)2-NSs and an appropriate amount of iridium trichloride hydrate (3 mg) were weighed and dispersed in 200 mL of deionized water and ultrasonically treated for 20 min until mixed evenly; then NaBH4 solution (10 mL, 0.13 g / mL) was added and stirred at a constant temperature of 60°C in a water bath for 6 hours; finally, the precipitate was collected by centrifugation and water washing to obtain Ir-NCs / Ni(OH)2-NSs.
[0073] S3. Phosphate treatment:
[0074] In an argon atmosphere, 125 mg of NaH2PO2·H2O and 100 mg of Ir-NCs / Ni(OH)2-NSs were placed in the crucibles at the upper and lower tuyere of a tube furnace, respectively. The temperature was then raised to 320°C at a rate of 2°C / min and kept for 2 hours to obtain Ir microcrystal-modified Ni2P ultrathin nanosheets (Ir-NCs / Ni2P-NSs).
[0075] Figure 1 This is a morphology of the Ir-NCs / Ni2P-NSs synthesized in Example 1. The size of the Ir crystallites is 3-5 nm and is evenly dispersed on the surface of the Ni2P ultrathin nanosheets with a thickness of about 1.7 nm.
[0076] Comparative Example 1: Ir-NCs / Ni(OH)2-NSs were prepared by the same steps as S1 and S2 of Example.
[0077] Comparative Example 2: Ni2P-NSs was prepared by the same steps as S1 and S3 of Example.
[0078] Comparative Example 3: Ni(OH)2-NSs was prepared in the same manner as step S1 of Example 1.
[0079] Comparative Example 4: A single-component IrCl3 solution (60 mL, 0.01 M) was reduced using NaBH4 solution (100 mL, 0.13 g / mL) to obtain Ir-NCs.
[0080] Comparative Example 5: Commercial 20 wt.% Pt / C catalyst purchased from the market.
[0081] (1) HER performance test
[0082] The catalysts of Example 1 and Comparative Examples 1-5 were tested by linear sweep voltammetry (LSV). The test conditions were as follows: the reference electrode was Hg / HgO, the counter electrode was graphite, the working electrode was a glassy carbon electrode, the scan rate was 10 mV / s, the voltage range was 0 ~ -0.5 V (vs RHE), the electrolyte was 1 M KOH solution, and the catalyst loading on the glassy carbon electrode was 0.11 mg / cm 2 .
[0083] The results are as follows Figure 2 As shown, Ir-NCs / Ni2P-NSs represents the LSV curve of the composite catalyst Ir-NCs / Ni2P-NSs prepared in Example 1, Ir-NCs / Ni(OH)2-NSs represents the LSV curve of the catalyst Ir-NCs / Ni(OH)2-NSs prepared in Comparative Example 1, Ni2P-NSs represents the LSV curve of the catalyst Ni2P-NSs prepared in Comparative Example 2, Ni(OH)2-NSs represents the LSV curve of the catalyst Ni(OH)2-NSs prepared in Comparative Example 3, Ir-NCs represents the LSV curve of the catalyst Ir-NCs prepared in Comparative Example 4, and Pt / C represents the LSV curve of the commercial 20wt.% Pt / C catalyst prepared in Comparative Example 5. Figure 2 It can be seen that when the electrolyte is 1 M KOH solution, the composite electrocatalyst Ir-NCs / Ni2P-NSs exhibits excellent HER electrocatalytic activity comparable to that of commercial Pt / C catalysts.
[0084] (2) EthOR performance test
[0085] The catalysts of Example 1 and Comparative Examples 2 and 4 were tested by linear sweep voltammetry (LSV). The test conditions were as follows: the reference electrode was Hg / HgO, the counter electrode was graphite, the working electrode was a glassy carbon electrode, the scan rate was 10 mV / s, the voltage range was 0-1.64 V (vs RHE), the electrolyte was a 1 M KOH solution containing 0.5 M ethanol, and the loading amount of the catalyst on the glassy carbon electrode was 0.11 mg / cm 2 .
[0086] The results are as follows Figure 3 As shown, Ir-NCs / Ni2P-NSs represents the LSV curve of the composite catalyst Ir-NCs / Ni2P-NSs prepared in Example 1, Ni2P-NSs represents the LSV curve of the catalyst Ni2P-NSs prepared in Comparative Example 2, and Ir-NCs represents the LSV curve of the catalyst Ir-NCs prepared in Comparative Example 4. Figure 3 It can be seen that in the electrolyte of 1 M KOH solution containing 0.5 M ethanol, Ir-NCs / Ni2P-NSs showed higher activity towards EthOR compared with Ir-NCs and Ni2P-NSs.
[0087] (3) Electrolytic cell voltage
[0088] The catalysts of Example 1 and Comparative Example 5 were tested using linear sweep voltammetry (LSV):
[0089] Test Example 1: Using 1 M KOH solution containing 0.5 M ethanol as the electrolyte, a symmetrical ethanol electrolyzer (Ir-NCs / Ni2P-NSs||Ir-NCs / Ni2P-NSs) was constructed. Figure 4 Ir-NCs / Ni2P-NSs||Ir-NCs / Ni2P-NSs (KOH+Eth) in the graph represents the LSV curve of this test case;
[0090] Test Example 2: Using 1M KOH solution as the electrolyte, a symmetrical water electrolyzer (Ir-NCs / Ni2P-NSs||Ir-NCs / Ni2P-NSs) was constructed. Figure 4 Ir-NCs / Ni2P-NSs||Ir-NCs / Ni2P-NSs(KOH) in the graph represents the LSV curve of this test case;
[0091] Test Example 3: Using 1M KOH solution as the electrolyte, a commercial Pt / C||RuO2 water electrolyzer (Pt / C||RuO2) was constructed. Figure 4 Pt / C||RuO2(KOH) in FIG. 5 represents the LSV curve of this test example.
[0092] The results are as follows Figure 4As shown, in an ethanol-containing electrolyzer, the voltage required for the symmetric Ir-NCs / Ni2P-NSs||Ir-NCs / Ni2P-NSs to reach a specific current density is lower than that of the corresponding hydrolyzer and the commercial Pt / C||RuO2 hydrolyzer.
[0093] The EthOR product in Test Example 1 was tested by NMR. Figure 5 As shown, the upper spectrum is the NMR spectrum of the electrolyte after the start of the timing current, and the lower spectrum is the NMR spectrum of the electrolyte before the start of the timing current. According to the NMR detection results, the characteristic peaks of acetate can be observed, which confirms that ethanol is oxidized into acetic acid and generates potassium acetate as an additional product at the anode.
[0094] It should be understood that the application of the present application is not limited to the above examples. For ordinary technicians in this field, improvements or changes can be made according to the above description, and all these improvements and changes should fall within the scope of protection of the present application.
Claims
1. A method for preparing a composite electrocatalyst, characterized in that: The following steps are involved: S1, preparation of Ni(OH)2 ultrathin nanosheets; S2, modifying the Ni(OH)2 ultra-thin nanosheets with iridium microcrystals by an in-situ reduction method to obtain Ni(OH)2 ultra-thin nanosheets modified with iridium microcrystals, wherein the diameter of the iridium microcrystals is 3-5 nm; S3, phosphating the Ni(OH)2 ultrathin nanosheets modified with iridium microcrystals to obtain Ni2P ultrathin nanosheets modified with iridium microcrystals, i.e., the composite electrocatalyst; Step S3 specifically includes the following steps: In an argon atmosphere, the phosphite and the iridium microcrystal-modified Ni(OH)2 ultrathin nanosheets are placed in crucibles at the upper and lower tuyere of a tubular furnace, respectively, and then heated to 300-320°C at a rate of 1-5°C / min and kept warm for 1-2 hours to obtain the iridium microcrystal-modified Ni2P ultrathin nanosheets.
2. The method for preparing the composite electrocatalyst according to claim 1, characterized in that: The mass ratio of nickel element to iridium element in the Ni2P ultra-thin nanosheet modified with iridium microcrystals is 20-100:1, and the thickness of the Ni2P ultra-thin nanosheet is between 1.5-2.5 nm.
3. The method for preparing the composite electrocatalyst according to claim 1, characterized in that: Step S1 specifically The following steps are involved: At room temperature, take nickel chloride solution and nickel potassium cyanide solution and mix them evenly, let them stand for 6-12 hours to obtain blue jelly-like NiCl2-K2Ni(CN)4 mixed cyanide glue; Pour the NaBH4 solution into the NiCl2-K2Ni(CN)4 mixed cyanide gel, stir vigorously in a 60-80°C water bath for 3-7 hours, collect the precipitate by centrifugation to obtain the Ni(OH)2 ultra-thin nanosheets, wash them alternately with deionized water and 0.1 M KOH several times, and dry them at 50-60°C.
4. The method for preparing the composite electrocatalyst according to claim 3, characterized in that: The molar ratio of nickel chloride to potassium nickel cyanide is 2:1, the concentration of the nickel chloride solution is 1-2 mM, the concentration of the potassium nickel cyanide solution is 0.5-1 mM, the concentration of the NaBH4 solution is 0.1-2 g / ml, and the ratio of the sum of the molar ratios of the NaBH4 to the nickel chloride and the potassium nickel cyanide is 10-30:
1.
5. The method for preparing the composite electrocatalyst according to claim 1, characterized in that: Step S2 specifically includes the following steps: Dispersing the Ni(OH)2 ultrathin nanosheets and iridium source in deionized water, and ultrasonically treating until the mixture is uniform; Add NaBH4 solution and stir in a water bath at 50-70℃ for 4-10 hours; The Ni(OH)2 ultra-thin nanosheets modified with the iridium microcrystals are collected by centrifugal washing.
6. The method for preparing the composite electrocatalyst according to claim 5, characterized in that: The mass ratio of the nickel element in the Ni(OH)2 ultra-thin nanosheet to the iridium element in the iridium source is 20-100:1; the concentration of the NaBH4 solution is 0.05-10 g / ml, the molar ratio of the NaBH4 to the iridium element is 550-3500:1, and 10-300 ml of the deionized water is added to every 100 mg of the Ni(OH)2 ultra-thin nanosheet.
7. The method for preparing the composite electrocatalyst according to claim 1, characterized in that: 0.1-0.5 g of phosphate salt is used for every 0.1 g of the iridium microcrystal-modified Ni(OH)2 ultra-thin nanosheets; the phosphate salt is one of sodium phosphate, sodium hypophosphite, and potassium phosphate.
8. A composite electrocatalyst, characterized in that: The composite electrocatalyst is prepared by the preparation method according to any one of claims 1 to 7.
9. Use of the composite electrocatalyst as claimed in claim 8, characterized in that: The composite electrocatalyst is used for water electrolysis to produce hydrogen or ethanol oxidation reaction.
